PERFORMANCE OF FORAGE CACTUS SUBMITTED TO DIFFERENT LEVELS OF IRRIGATION AND ORGANIC FERTILIZATION IN THE SEMI-ARID REGION OF PARAIBA (Colloquium Agrariae. ISSN: 1809-8215, 2022)
The forage cactus represents one of the main sources of fodder for livestock in the semi-arid region. However, although it is cultivated on a large scale in several regions, there are still few studies addressing issues of improved management, especially about irrigation and fertilization of recently used varieties, such as those resistant to false carmine cochineal. Thus, this research aimed to evaluate the effect of different levels of irrigation and sources of organic fertilizer on the productive performance of forage cactus variety Mexican Elephant’s Ear (Opuntia stricta). The experiment was set up at Fazenda Riachão, municipality of Boa Vista, Paraíba. Two types of manure (bovine and caprine) and the control were used, associated with the absence of irrigation and five different blades, which varied from 1.5 to 5.5 L of water per week per plant. A 3x6 factorial design with five repetitions was used in a randomized block design. The blades of water applied promoted a significant increase in the variables analyzed. The goat manure was the most effective in obtaining better values of the number of cladodes per plant and productivity.